Treatment Effect Heterogeneity in Theory and Practice - Joshua D. Angrist (Institute for the Study of Labor (IZA), 2003)
Instrumental Variables (IV) methods identify internally valid causal effects for individuals whose treatment status is manipulable by the instrument at hand. Inference for other populations requires homogeneity assumptions. This paper outlines a theoretical framework that nests causal homogeneity assumptions. These ideas are illustrated using sibling-sex composition to estimate the effect of child-bearing on economic and marital outcomes. The application is motivated by American welfare reform. The empirical results generally support the notion of reduced labor supply and increased poverty as a consequence of childbearing, but evidence on the impact of childbearing on marital stability and welfare use is more tenuous.
Keywords: J12; J13; C31; 330; instrumental variables; marital stability; welfare; causal effects; Instrumentalvariablen-Schätzmethode; Kausalanalyse; Fruchtbarkeit; Sozialhilfeempfänger; Sozialhilfe; Schätzung; Vereinigte Staaten